Stabilnost antenskega stebra ob upoštevanju hkratnega delovanja lastne teže in zunanje obremenitve - Saucha, Juraj (Strojniški vestnik, 2001)
This paper deals with the determination of the elastic stability of an antenna column subjected to the simultaneous actions of its own weight and an effective load as an axial compressive force was based upon the solution to the governing differential equation of the column in the form of a Maclaurin's series with a rapid convergence due to the introduced substitution.The obtained results, with a quality of the exact solution to the governing differential equation, were relevant for the evaluation of the accuracy of the approximate solution which assumed the linear interaction of the weight of the column and axial compressive force. It has been established that the approximate solution differed from the results obtained in this paper by-2%.
Keywords: stebri antenski; stabilnost; obremenitve kritične; enačbe diferencialne; nosilne konstrukcije; konstruiranje; antene; diferencialne enačbe